Dynamic response investigation of PV based CLCIS fed IMD applications using HC and SMC - Rajamanickam Pazhanimurugan; Ramaiyan Bensraj; Chinnapettai Ramalingam Balamurugan (Bulletin of Electrical Engineering and Informatics, 2022)
This paper explains a solar photovoltaic (SPV) based cascaded landsman converter inverter structure (CLCIS) which feeds induction motor drive (IMD) using hysteresis controller (HC) and sliding mode controller (SMC). The aim is to create SPV based cascaded landsman converter (CLC) with an enhanced dynamic response. HC and SMC enabled systems are designed and created using MATLAB. The standards of procedure and simulation results are examined. The simulation results of HC and SMC enabled systems are analyzed concerning time-domain parameters and a comparison has been exhibited. The proposed SMC ensures a model reference robust dynamics against changing voltage conditions of photovoltaic (PV) based CLCIS fed IMD system. The consequences reveal that the dynamic response with SMC is better compared to the HC enabled CLCIS-IMD system.